2015
DOI: 10.1371/journal.pone.0117206
|View full text |Cite
|
Sign up to set email alerts
|

Brain Expressed and X-Linked (Bex) Proteins Are Intrinsically Disordered Proteins (IDPs) and Form New Signaling Hubs

Abstract: Intrinsically disordered proteins (IDPs) are abundant in complex organisms. Due to their promiscuous nature and their ability to adopt several conformations IDPs constitute important points of network regulation. The family of Brain Expressed and X-linked (Bex) proteins consists of 5 members in humans (Bex1-5). Recent reports have implicated Bex proteins in transcriptional regulation and signaling pathways involved in neurodegeneration, cancer, cell cycle and tumor growth. However, structural and biophysical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…BEX1 (brain expressed X-linked 1) plays a role in neuronal and myoblast development and has been reported to be a marker for NE cells (47,48). However, it may play a wider role and be involved in cell cycle control and act as a tumor suppressor gene in some situations (49).…”
Section: Discussionmentioning
confidence: 99%
“…BEX1 (brain expressed X-linked 1) plays a role in neuronal and myoblast development and has been reported to be a marker for NE cells (47,48). However, it may play a wider role and be involved in cell cycle control and act as a tumor suppressor gene in some situations (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, BEX2 is highly expressed in a subset of estrogen receptor-positive breast cancers 10 and glioblastoma 11 and plays a key role in promoting cell survival and growth in breast cancer cells. The BEX protein family has been reported to contain long regions of intrinsic disorder that may form signaling hubs, and the hubs formed by intrinsically disordered proteins play important roles in cellular differentiation and cancer 6. Thus, BEX2 appears to play different roles in different tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-expressed X-linked (BEX) genes are a family of genes that reside on the mammalian X chromosome, and BEX proteins are involved in the cell cycle, cancer and tumor growth 6,7. BEX2 is highly expressed in the embryonic brain and can interact with transcriptional factor LMO2 to regulate transcriptional activity 8.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that OMP modulated Ca 2+ -mediated PKC/ MAPK signaling, which is the main pathway responsible for TRH-induced PRL expression. Previous studies have shown that OMP modulates Ca 2+ extrusion from olfactory sensory neurons by directly interacting with brainexpressed X-linked 1 (Bex1) proteins, which can also bind to the Ca 2+ -dependent modulator, calmodulin (CaM) 8,11,13,39,40 . The OMP-Bex1-CaM interaction can explain the desensitization to TRH stimulation that is observed in the absence of OMP.…”
Section: Discussionmentioning
confidence: 99%